Proteomic Identification of Annexins, Calcium-Dependent Membrane Binding Proteins That Mediate Osmotic Stress and Abscisic Acid Signal Transduction in Arabidopsis - Lee, Sumin (American Society of Plant Biologists, 2004)
Comparative proteomic analysis of the Arabidopsis thaliana root microsomal fraction was performed to identify novel components of salt stress signaling. Among the salt-responsive microsomal proteins, two spots that increased upon salt treatment on a two-dimensional gel were identified as the same protein, designated annexin 1 (AnnAt1). Annexins comprise a multigene family of Ca(2+)-dependent membrane binding proteins and have been extensively studied in animal cells. AnnAt1 is strongly expressed in root but rarely in flower tissue. In this study, the results suggest that salt stress induces translocation from the cytosol to the membrane and potential turnover of existing protein. This process is blocked by EGTA treatment, implying that AnnAt1 functions in stress response are tightly associated with Ca(2+). T-DNA insertion mutants of annAt1 and a different isoform, annAt4, displayed hypersensitivity to osmotic stress and abscisic acid (ABA) during germination and early seedling growth. The results collectively suggest that AnnAt1 and AnnAt4 play important roles in osmotic stress and ABA signaling in a Ca(2+)-dependent manner.